Pengaruh Customer Relationship Marketing, Brand Awareness dan Price Perception Terhadap Buying Decision (Studi Kasus Konsumen Brand Skincare Somethin C) - Made Mulyadi Mulyadi; Ni Luh Putu Rahayu Mardiana Sari; I Nyoman Rasmen Adi; Luh Gede Elvina Adi Saputri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The growth and development of beauty and skin care products from Indonesia has advanced, therefore there are more and more competitors from well-known local brands from Indonesia. This can be seen from the competition offered such as the price offered, the quality and benefits offered and so on. The purpose of this study was to determine the effect of customer relationship marketing, brand awareness, price perception on buying decisions on consumers of the SomethinC skincare brand. This research method uses quantitative research methods on 95 consumers of the SomethinC skincare brand in the Badung district, Bali Province. The results of this study state that customer relationship marketing has a positive and significant effect on buying decisions, brand awareness has a positive and significant effect on buying decisions, price perception has a positive and significant effect on buying decisions and simultaneously customer relationship marketing, brand awareness, price perception have a positive effect. and significant to the buying decision.